SINERGI ORANG TUA DAN PERGURUAN TINGGI HINDU DALAM MENINGKATKAN MUTU PERGURUAN TINGGI HINDU - Bali Sastrawan, Ketut (LPM IHDN Denpasar, 2015)
National character and civilization building cannot be separated from the education institution. As a place for producing intellectuals, educationinstitutions might be regarded as the â€œsecond homesâ€ in which students study to develop their competencies. They are the places in which the collaboration from the studentsâ€™ parents is needed in order to create a good learning atmosphere. So far the Hindu education institutions receive lack of this kind of collaboration. As a solution, it is necessary to provide more space for the studentsâ€™ parents to contribute to the Hindu higher educationimprovement. Such a place is necessary for a good communication as in a particular situation studentsâ€™ parents should be involved in improving the quality of the education and avoiding opposition.